Thyroid Hormone - Kumar Agrawal, Neeraj (IntechOpen, 2012)
Thyroid hormone is important for controlling metabolism and many other body functions. Changes in thyroid hormone physiology, its regulation and diseases thereof have been a concern for the mankind. Understanding of the thyroid hormone(s) has been continuously updated and revised. The contributions from different authors have been incorporated in this book for this purpose. The original work of these contributors will be especially useful in furthering the knowledge on thyroid and help in creating new vistas of research.